2021
DOI: 10.1111/1462-2920.15639
|View full text |Cite
|
Sign up to set email alerts
|

Growth promotion of a deep‐sea bacterium by sensing infrared light through a bacteriophytochrome photoreceptor

Abstract: Photoreceptors are found in all kingdoms of life and bacteriophytochromes (Bphps) are the most abundant photo-sensing receptors in bacteria. Interestingly, BphPs have been linked to some bacterial physiological responses, yet most of the biological processes they regulate are still elusive, especially in non-photosynthetic bacteria. Here, we show that a bacteriophytochrome (CmoBphp) from a deep-sea bacterium Croceicoccus marinus OT19 perceives infrared light (wavelength at 940 nm) and transduces photo-sensing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 41 publications
0
10
0
Order By: Relevance
“…4C ): the expression of a majority of genes associated with phototrophic apparatus was significantly upregulated when the cells were exposed to the deep-sea potentially illuminous environment. Actually, there is plenty of evidence showing that both long-wavelength (>650 nm) ( 38 , 39 ) and short-wavelength (<650 nm) ( 2 ) light have been detected in deep sea ( 40 ). Thus, the necessary conditions for light-associated metabolisms are met in these environments.…”
Section: Discussionmentioning
confidence: 99%
“…4C ): the expression of a majority of genes associated with phototrophic apparatus was significantly upregulated when the cells were exposed to the deep-sea potentially illuminous environment. Actually, there is plenty of evidence showing that both long-wavelength (>650 nm) ( 38 , 39 ) and short-wavelength (<650 nm) ( 2 ) light have been detected in deep sea ( 40 ). Thus, the necessary conditions for light-associated metabolisms are met in these environments.…”
Section: Discussionmentioning
confidence: 99%
“…An important hint that supports our hypotheses is that bacteria from the deep-sea, and therefore living in the non-photic zone, possess photoreceptors that mediate light-behavioural responses. For example, it has been shown that some deep-sea species possess either PYP or bacteriophytochrome photoreceptors that regulate biofilm formation or growth [ 225 , 226 ]. While these studies have proposed that these photoreceptors contribute to the regulation of their benthic and pelagic lifestyle, they may also make bacteria sensitive to bioluminescence in the non-photic zone.…”
Section: Hypothesis: Bioluminescence Signalling In the Unicellular Worldmentioning
confidence: 99%
“…Interestingly, the important effect of blue-light on bacteria has led to light-based anti-infective strategies being conceived [ 221 , 222 , 223 , 224 ]. However, particularly relevant for the present review is the finding that deep-sea bacteria that usually live in the non-photic zone possess photoreceptors and respond to light [ 225 , 226 ]. While it has been proposed that these deep-sea chemoreceptors may help to switch the behaviours between a planktonic and a benthic lifestyle, this finding may also support the hypothesis that bacteria perceive the bioluminescence of other deep-sea organisms, including themselves, which is the unique source of light in deep-sea sediments.…”
Section: Introductionmentioning
confidence: 99%
“…Photosensory proteins, as receptors of light, perceive and transmit the color and intensity of signals from ambient light ( 3 ). Subsequent studies have revealed that photosensors of other classes are functional in nonphototrophic bacteria, including the light-oxygen-voltage (LOV) domain protein (blue light sensing) ( 5 ), photoactive yellow protein (PYP) (blue light sensing) ( 6 ), blue light using flavin-adenine dinucleotide (FAD) (BLUF) domain proteins ( 7 ), and bacteriophytochrome (infrared light sensing) ( 8 ). BLUF was even proposed to function in a marine photosynthetic gammaproteobacterium ( Congregibacter litoralis KT71 T ) ( 9 11 ).…”
Section: Introductionmentioning
confidence: 99%
“…As a result, the photosensing system of mesopelagic microorganisms has been pushed to its sensitivity limits to function in this extreme environment. For example, in the deep-sea hydrothermal vents, a nonphototrophic bacterium, Croceicoccus marinus OT19, that senses infrared light (wavelength, 940 nm) by the bacteriophytochrome has been reported ( 8 ). Compared to the hydrothermal vents, in the deep-sea cold seeps, short-wavelength and long-wavelength downwelling light are rapidly attenuated by seawater and gradually disappear along with the increasing depth, and the remaining light is mainly blue-green light ( 20 ).…”
Section: Introductionmentioning
confidence: 99%